What marks the beat of speech? - Kochanski, G; Orphanidou, C (Acoustical Society of America, 2008)
Which acoustic properties of the speech signal differ between rhythmically prominent syllables and non-prominent ones? A production experiment was conducted to identify these acoustic properties. Subjects read out repetitive text to a metronome, trying to match stressed syllables to its beat. The analysis searched for the function of the speech signal that best predicts the timing of the metronome ticks. The most important factor in this function is found to be the contrast in loudness between a syllable and its neighbors. The prominence of a syllable can be deduced from the specific loudness in an (approximately) $360$~millisecond window centered on the syllable in question relative to an (approximately) $800$~millisecond-wide symmetric window.